If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 6y + 9 = 2(2y + 3) Reorder the terms: 9 + 6y = 2(2y + 3) Reorder the terms: 9 + 6y = 2(3 + 2y) 9 + 6y = (3 * 2 + 2y * 2) 9 + 6y = (6 + 4y) Solving 9 + 6y = 6 + 4y Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '-4y' to each side of the equation. 9 + 6y + -4y = 6 + 4y + -4y Combine like terms: 6y + -4y = 2y 9 + 2y = 6 + 4y + -4y Combine like terms: 4y + -4y = 0 9 + 2y = 6 + 0 9 + 2y = 6 Add '-9' to each side of the equation. 9 + -9 + 2y = 6 + -9 Combine like terms: 9 + -9 = 0 0 + 2y = 6 + -9 2y = 6 + -9 Combine like terms: 6 + -9 = -3 2y = -3 Divide each side by '2'. y = -1.5 Simplifying y = -1.5
| 2.4X-37=1.9X+4 | | 3x+6=-30-3x | | 3x-33=2x+28 | | 1600=200+.75y-75+x | | 1.4X=4.2 | | (2x-4)2=12 | | -4-6k=-4+4k+6k | | 1+11x=11+x | | -3(2-7x)=40-2x | | 73-2x=87-3x | | 2p-7p=4-2p-2p | | -4(6v-2)=-8v-40 | | 90=x^2+x | | 1+3n+5=-4+4+n-n | | 2x-7=7x+11 | | 4+3y-1=9y+6-5y | | 15x-10=5x | | 4e(2e-5)= | | 4y-4-(-y)-9y= | | -6-5a=-(7a-4) | | x^2+22x+112-x^2-6x=544 | | 4.9x=29.4 | | 4x^2-11x-2=0 | | -8(8-8r)=-8+8r | | 5.9+x=-6.4 | | 4+3-1=9y+6-5y | | 4(1-2-3)=7(2-3+10) | | 0.17x+0.22=1.58 | | 14-5r=6 | | 5x+(-8x)+3-x= | | x^6-2x^4+5x^2-5=0 | | 5m+1= |